Full thickness open tear of the tendoachilles - Functional outcomes following a stable, single stage repair - Baindoor, Prasanna (J Clin Orthop Trauma, 2020)
OBJECTIVE: Open injuries of the Tendoachilles present a challenge to the treating surgeon. Although, common in our setting, there is a paucity of literature regarding management of the same. The purpose of this retrospective study was to analyse the functional outcomes following debridement and primary repair of open tears of the Tendoachilles. MATERIALS AND METHODS: Patients with open tears of the tendoachilles, between January 2012 to January 2017. After obtaining demographic data, including mechanism of injury, all patients were managed by adequate debridement and primary repair, by Pennington’s modification of Kessler’s technique in a single sitting, paratenon closed circumferentially, plantaris reinforcement used when end to end repair couldn’t be achieved. Below knee cast for 2 months. Weight bearing started at three months. Statistical analysis using paired t-test for calf circumference, ankle range of motion comparing with uninjured limb. Functional outcome assessment by AOFAS hindfoot score and Achilles tendon rupture score. RESULTS: 23 male patients, mean age 35, were analysed. Field injury was the most common mechanism, with slip in Indian lavatory pans accounting for four patients. Average time to surgery from injury was 22 hours. Plantaris reinforcement in one case. No case of wound dehiscence, scar adherence, tendon rerupture or infection. One patient had serous discharge at three weeks which settled with oral antibiotics. 21 patients performed single heel raise. There was no significant difference in calf circumference and ankle range of motion compared to uninjured limb. Mean AOFAS score was 92, mean Achilles tendon rupture score 77. CONCLUSION: Though open injuries of the tendoachilles is fraught with complications, early debridement, adequate repair of the tendon edges with circumferential closure of the paratenon, yields adequate functional outcomes with minimal complications.